2010
DOI: 10.1080/01426397.2010.519436
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Preferences towards Potential Future Landscapes in the Swiss Alps

Abstract: Land abandonment followed by spontaneous reforestation has been an ongoing process in the Swiss Alps, especially on steep and relatively inaccessible slopes and on alpine summering pastures. This study aims to identify and explain differences in preferences towards potential future landscapes: 1) between landscape settings at different elevation belts (e.g. valley bottom, forest clearings at medium elevations, alpine pastures above the forest belt); 2) between a group of local residents and the general Swiss p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
35
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 30 publications
7
35
0
Order By: Relevance
“…The participants were on average better educated than the Swiss population, and members of environmental organisations were over-represented. Such differences were also found in other studies (Soliva, Bolliger, & Hunziker, 2010;Junge et al, 2011). Farmers were also strongly over-represented and showed their strong interest in this study.…”
Section: Data Collection and Respondentssupporting
confidence: 66%
See 1 more Smart Citation
“…The participants were on average better educated than the Swiss population, and members of environmental organisations were over-represented. Such differences were also found in other studies (Soliva, Bolliger, & Hunziker, 2010;Junge et al, 2011). Farmers were also strongly over-represented and showed their strong interest in this study.…”
Section: Data Collection and Respondentssupporting
confidence: 66%
“…Other studies have also shown a strong influence of landscape characteristics on preference ratings (overview in Due to non-response, our sample is not free from bias, reducing the representativeness of the results. However, non-response bias is difficult to avoid in postal surveys and a response rate of 39% is actually high for nature-related postal surveys in Switzerland, where rates of 25% and lower are much more common (see, e.g., Soliva et al, 2010). The over-representation of, e.g., farmers and members of environmental organizations shows their strong interest in this study.…”
Section: Many Researchers Argue That Humans Have An Innate Preferencementioning
confidence: 99%
“…Augmented photos and other visualizations have been used to evaluate and discuss alternative planning options for specific locations [e.g., 117], including examination of the impacts of potential land-management options on people's perceptions [e.g., 46,118,119]. Spatially explicit land change scenarios can also be translated into 3D landscape visualizations that can then be evaluated by stakeholders [120,121].…”
Section: Modeling Landscape Changementioning
confidence: 99%
“…3). These photo-realistic images have been particularly helpful in comparison and change studies [46]. Such images enable evaluation of specific landscape elements and ensure that extraneous factors like ambient light, skyline, and cloud cover, which are factors known to influence cognitive and esthetic responses, do not influence responses [44].…”
Section: Photo-based Visualizationsmentioning
confidence: 99%
“…Removal of habitat elements in agricultural landscapes not only reduces the area available as habitats but also results in ecosystem fragmentation, which is a process that describes the emergence of (Brown 2006;Soliva et al 2010;Howley et al 2012;Van Berkel and Verburg 2012), although Hartig and Staats (2005) point out that there are also consistencies in preferences for natural landscapes that appear to be common to humanity. People tend to prefer landscapes that contain a moderate to high degree of complexity (Ulrich 1983;Kaplan and Kaplan 1989;Hunziker 1995;Hunziker and Kienast 1999), with a variety of elements (Misgav 2000) and a degree of management (Ulrich 1986;Gobster 1995).…”
Section: Introductionmentioning
confidence: 99%